2005
DOI: 10.5458/jag.52.115
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of Ferulic Acid from Sugar Beet Pulp Using the Culture Supernatant of Penicillium chrysogenum

Abstract: Ferulic acids have been found in the cell walls of many plant products including maize bran, 1) sugar cane bagasse,2) wheat bran, 3) sugar beet pulp, 4,5) and spinach. 6) In the three former tissues, ferulic acid is esterified to the C 5 of arabinose in arabinoxylan, a 1,4 D xylan to which L arabinofuranosyl residues are attached at position 2 or 3. In contrast, ferulic acids mainly attach to the C 2 position of 1,5 linked arabinofuranose residues or the C 6 of 1,4 linked galactopyranose residues in the hairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
1
5
0
2
Order By: Relevance
“…3B). This is similar to earlier findings shown for Penicillium chrysogenum [26], Aspergillus niger [27,28] and Aspergillus oryzae [29] esterases. However, the optimum temperature of Geobacillus sp TF17 esterase is higher than the esterases from Cucurbita pepo Elc and Ell with an optimum temperature between 30 and 40°C [30] and some Bacillus sp.…”
Section: Effect Of Ph and Temperature On Enzyme Activitysupporting
confidence: 81%
“…3B). This is similar to earlier findings shown for Penicillium chrysogenum [26], Aspergillus niger [27,28] and Aspergillus oryzae [29] esterases. However, the optimum temperature of Geobacillus sp TF17 esterase is higher than the esterases from Cucurbita pepo Elc and Ell with an optimum temperature between 30 and 40°C [30] and some Bacillus sp.…”
Section: Effect Of Ph and Temperature On Enzyme Activitysupporting
confidence: 81%
“…FAEs in the Tannase family were once considered to have type C specificity (active on MFA, MSA, M p CA, and MCA) . However, according to current knowledge, only one member of the Tannase family, FaeC from Talaromyces sipitatus ( Ts FaeC), has the typical type C specificity, and the rest of FAEs exhibit very weak or no activity against MSA (type B or type B‐like specificities) . Ao FaeC and Fo FaeC‐12213 from Fusarium oxysporum were reported to have type C specificity .…”
Section: Resultsmentioning
confidence: 99%
“…Elucidating the functions of these l-arabinan-degrading enzymes and harnessing these functions may therefore improve the commercial production of l-arabinose from industrial by-products. In addition to arabinanolytic enzymes, we have found that P. chrysogenum produces various pectolytic enzymes, such as ␤-1,4-galactanases [35], rhamnogalacturonan lyases [36,37], pectin and pectate lyases (unpublished results), and a ferulic acid esterase [19]. Pectolytic enzymes are useful for the processing of plant materials, such as fruit juice clarification, and for preparation of functional oligosaccharides, modulation of the properties of pectins, and analysis of pectin structures [38].…”
Section: Discussionmentioning
confidence: 96%
“…O-␣-l-arabinofurnosyl-(1→3)-O-[2-O-(feruloyl)-␣-larabinofurannosyl]-(1→ 5)-l-arabinofuranose (feruloylated branched Ara3) was prepared from sugar beet pulp by treatment with Driselase (ASKA Pharmaceutical CO., Ltd., Tokyo, Japan), as described previously [18]. Feruloylated branched Ara3 was digested with the ferulic acid esterase (FAE-1) from P. chrysogenum 31B [19], yielding branched Ara3.…”
Section: Substratesmentioning
confidence: 99%